Theoretical Research on the Impact of Country Risk on Insurance Demand - Li, Bofang (Advances in Social Sciences Research Journal, 2021)
Derive the optimal premium expenditure of the insured from the consumer expected utility maximization model. On this basis, the concept of country risk is introduced, and derive the optimal premium expenditure of the insured in the presence of country risk is. Then compare the optimal premium expenditure of the insured when there is country risk and when there is no country risk, and study the impact of country risk on insurance demand.